ANALYSIS OF ORGANIC VEGETABLE CULTIVATION BUSINESS DEVELOPMENT STRATEGY (SANALYSIS OF ORGANIC VEGETABLE CULTIVATION BUSINESS DEVELOPMENT STRATEGY (CASE STUDY: FARMER GROUP IN OABIKASE VILLAGE, INSANA BARAT DISTRICT, TTU REGENCY) - Elfrida Desiderata Naihati (Jurnal Scientia, 2023)
In line with the development of science and technology, many new discoveries have shifted the traditional farming system to a conventional farming system. Conventional farming systems are characterized by the use of inorganic inputs and agrochemicals in the cultivation process. Community understanding of the negative impacts of conventional agriculture both on the environment and health has awakened people to return to living in a healthy and natural way or what is now better known as back to nature. The purposes of this research are: (1) Identify what internal and external factors are the strengths and weaknesses as well as what threats and opportunities will be faced by the Atapain farmer group, (2) Formulate and prioritize the best strategies that can be implemented and recommended to Atapain farmer group. The data used in this study are primary data and secondary data. Primary data was obtained from direct interviews with twenty respondents, while secondary data was obtained from reports from institutions that are closely related to organic vegetable business. Other supporting data were obtained from internet sites, magazine articles, newspapers, previous studies as comparative material as well as a collection of information from related agencies such as the Central Bureau of Statistics (BPS) and the Department of Agriculture. Data analysis was carried out qualitatively. This study identified the internal and external environmental factors that became the strengths and weaknesses as well as the opportunities and threats to be faced by farmer groups and the decision stage. Based on the results of the IFAS analysis, the appropriate alternative strategies that can be recommended for farmer groups are strengthening and maintaining existing marketing areas by maintaining product quality and maintaining good planting plans.